KARAKTERISTIK MUTU KUE NAGASARI DENGAN SUBTITUSI TEPUNG KACANG KEDELAI - Ni Made Putri Kusuma Dewi; Ni Putu Agustini; Hertog Nursanyoto (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Soybean flour is one alternative to increase the nutritional value that can be processed into a variety of processed foods. Nagasari cakes are generally made from rice flour, coconut milk, sugar, and salt. Comparison of soybean flour to rice flour can add nutritional value to Nagasari cake. This study aims to determine organoleptic characteristics including taste, color, aroma, texture, overall acceptance and texture quality of Nagasari cake, to determine the protein content of the best Nagasari cake, and calculate the nutrient content produced in 1 portion of the best Nagasari cake . This study uses an experimental method with a Randomized Block Design (RCBD). There are 5 treatments with a ratio of 5 grams of soybean flour, 10 grams, 15 grams, 20 grams, 25 grams to 95 grams of rice flour, 90 grams, 85 grams, 80 grams, 75 grams. Based on Variety Analysis (ANOVA), Nagasari cake with organoleptic quality on taste, color, aroma, texture, overall acceptance and texture quality significantly affected. In 50 grams of Nagasari cake contains 151.55 kcal energy, 2.15 gram protein, 1.39 gram fat and 31.92 gram carbohydrate. Nagasari cake with the substitution of the best characteristic soybean flour is the ratio of 5 gram soybean flour to 95 gram rice flour. Key words: Soybean flour, Nagasari cake, Protein